Evaluation of the non-use value of beach tourism resources: A case study of Qingdao coastal scenic area, China. (1st February 2019) - Liu, Jia; Liu, Ning; Zhang, Yumiao; Qu, Zheng; Yu, Jing
Abstract: Beaches, an important component of coastal tourism resources, are gradually eroding as a result of environmental pollution, ecological damage, etc., which is ignored by tourists as more recreational coastal activities become available. In this context, the present study attempts to investigate the willingness to pay (WTP) of tourists and evaluates the non-use value of beach tourism resources to protect beaches from further deterioration. Towards this aim, a scientific survey is implemented on the beaches of Qingdao coastal scenic area (China) with application of the contingent valuation method (CVM). In addition, this study uses a logistic regression model to analyze the factors affecting tourists' WTP. The results indicate that 80.8% of tourists would be willing to pay to preserve beach tourism resources, and the mean WTP is 10.0 (¥66.7) per year when zero values are considered. Factors such as tourists' gender and traveling frequency to the beaches significantly affect their WTP to preserve beach tourism resources, with females exhibiting a higher probability of paying than males, and those with a higher traveling frequency also present a higher probability of paying. The non-use value of beach tourism resources is estimated at 0.8 billion (¥5.4 billion), based on the total number of tourists in Qingdao in 2016 as the survey sample. Therefore, scientific evaluation of the non-use value of beach tourism resources is beneficial to the sustainable development and preservation of beaches. Highlights: The contingent valuation method (CVM) is used to estimate tourists' willingness to pay (WTP) and evaluate the non-use value of beach tourism resources in the Qingdao coastal scenic area, China. Among the surveyed tourists, 80.8% would be willing to pay to preserve beach tourism resources, and the mean WTP is 10.0 (¥66.7) per year. Tourists' gender and traveling frequency to beaches significantly affect tourists' WTP to preserve beach tourism resources, with females being more willing to pay than males and those who exhibit a higher traveling frequency also being more willing to pay. The non-use value of beach tourism resources is estimated at 0.8 billion (¥5.4 billion).